A longer duration of red blood cell storage is associated with a lower hemoglobin increase after blood transfusion: a cohort study. Issue 6 (21st February 2019) - Rydén, Jenny; Clements, Mark; Hellström‐Lindberg, Eva; Höglund, Petter; Edgren, Gustaf
Abstract : BACKGROUND: RBC concentrates are commonly stored for up to 42 days but there has been conflicting evidence on the effect of storage duration and clinical outcomes. Most clinical studies have focused on possible associations between duration of storage time and risk for adverse outcomes, including mortality. Recent clinical trials did not find any such associations, but fewer studies have addressed whether storage time affects component efficacy. The main aim of this study was to determine the effect of RBC storage time on hemoglobin increment in transfused patients. STUDY DESIGN AND METHODS: Transfusion data on a cohort of patients with myelodysplastic syndromes were linked to hemoglobin measurements taken between 2 days before and 28 days after a transfusion episode. We applied a mixed‐effect linear regression model, accounting for patient characteristics and time from transfusion to next hemoglobin measurement, to study the effect of RBC storage on the hemoglobin increment. RESULTS: The study population consisted of 225 patients who received 6437 RBC units. Compared to units stored less than 5 days, transfusion of blood units stored 5 to 9, 10 to 19, 20 to 29, or 30 or more days resulted in hemoglobin increases that were 0.83 (95% confidence interval [CI], 0.24–1.41), 0.92 (95% CI, 0.34–1.51), 1.33 (95% CI, 0.65–2.02) and 1.51 (95% CI, 0.58–2.43) g/L lower, respectively, per RBC unit. Results were consistent in sensitivity analyses. CONCLUSIONS: Longer RBC storage was associated with a smaller increase in hemoglobin concentration after transfusion. Although statistically significant, the effect was modest, and its clinical relevance in subgroups of patients should be investigated in prospective clinical trials.